Pioduran National High School (PDNHS) library development plan - Bachiller, Ross T.; Santos, Mark Anthony A.; Obille, Kathleen Lourdes B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2018)
Before the start of the project, Pioduran National High School (PDNHS) has a library that is not properly organized that would answer the information needs of its students and teachers. The reorganization of the PDNHS Library will be helpful in the instilling the importance of education and literacy to the students of PDNHS.
The general objective of the project is to reorganize the PDNHS Library. Its specific objectives include: 1) develop the library's objectives, based on the vision, mission and curriculum of PDNHS; 2) determine the existing conditions and needs of the PDNHS Library, in relation to its mission, goals and objectives, administration human resources, collection, services, physical facilities, information technology facilities and services, financial resources, and linkages and networking; 3) determine the instructional, research, and recreational needs of the PDNHS community; and 4) formulate written policies in relation to library administration and operation.
The descriptive research method was used to determine the information needs of the students of PDNHS. A survey questionnaire for the teachers and students was used to determine the information in the library. Interview with the Designated Librarian and document analysis were also utilized in this study.
Based on the ocular inspection and interview with the designated Librarian of PDNHS Library, PDNHS does not adhere to the Minimum Standards for School Libraries. Drafting of collection development policy, manual of operations of PDNHS Library and other set of policies, procedures, rules and regulations are highly recommended.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Library development plan; Pioduran National High School Library